2019
DOI: 10.1097/meg.0000000000001494
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of blood microbiota in patients with liver cirrhosis

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 20 publications
0
41
0
Order By: Relevance
“…Analysis of gut microorganisms revealed significant differences between CVT and SPF mice showing effective transfer of microorganisms from CVB to CVT mice through co-housing. The top three OTUs highly represented in CVB mice and effectively transferred to CVT mice during co-housing were Prevotellaceae, Lactobacillaceae and Rikenellaceae , which is consistent with our previous observation in CByB6F1 mice born and housed in the same conventional facility in which the same three microbial families were most abundant in CVB mice [ 17 ].These microbial families offer health benefits, since lack of Prevotellaceae and Rikenellaceae have been associated with Parkinson’s disease [ 21 ], and liver cirrhosis [ 22 ]. In Rag1-/- mice, fecal transplants from wild type donors altered gut bacterial community with increases in Prevotellaceae which were accompanied by increases in total number of BM cells and HSPCs [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of gut microorganisms revealed significant differences between CVT and SPF mice showing effective transfer of microorganisms from CVB to CVT mice through co-housing. The top three OTUs highly represented in CVB mice and effectively transferred to CVT mice during co-housing were Prevotellaceae, Lactobacillaceae and Rikenellaceae , which is consistent with our previous observation in CByB6F1 mice born and housed in the same conventional facility in which the same three microbial families were most abundant in CVB mice [ 17 ].These microbial families offer health benefits, since lack of Prevotellaceae and Rikenellaceae have been associated with Parkinson’s disease [ 21 ], and liver cirrhosis [ 22 ]. In Rag1-/- mice, fecal transplants from wild type donors altered gut bacterial community with increases in Prevotellaceae which were accompanied by increases in total number of BM cells and HSPCs [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cirrhosis dysbiosis ratio may be a useful quantitative indicator to describe the changes in the microbiome accompanying the progression of cirrhosis. Interestingly, a recent study has found that the diversity of circulating bacteria in patients with cirrhosis is consistent with the presence of dysbiosis in cirrhotics[ 155 ]. Moreover, specific taxa of gut microbes are associated with changes in neurons and astrocytes in brain dysfunction associated with cirrhosis[ 156 ].…”
Section: Microbiota-gut-live-brain Axis and Cirrhosis And Hementioning
confidence: 97%
“…Kajihara and coworkers examined the peripheral blood microbiota of patients with liver cirrhosis by 16S rRNA gene sequencing and found that while the abundance of Enterobacteriaceae was significantly increased, the abundance of Akkermansia, Rikenellaceae and Erysipelotrichales was decreased in cirrhotic patients (27).…”
Section: Non-intestinal Microbiotas and Liver Diseasesmentioning
confidence: 99%
“…Figure 2 Summary of studies on non-intestinal microbiotas in diverse liver diseases (24)(25)(26)(27)(28)(29)(30)(31). HCC, hepatocellular carcinoma.…”
Section: Biogeography Of the Liver Tissue Bacterial Dna Of Patients With Nafldmentioning
confidence: 99%